If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(7y + -1) + 5y = -2(3y + 4) + -3 Reorder the terms: -4(-1 + 7y) + 5y = -2(3y + 4) + -3 (-1 * -4 + 7y * -4) + 5y = -2(3y + 4) + -3 (4 + -28y) + 5y = -2(3y + 4) + -3 Combine like terms: -28y + 5y = -23y 4 + -23y = -2(3y + 4) + -3 Reorder the terms: 4 + -23y = -2(4 + 3y) + -3 4 + -23y = (4 * -2 + 3y * -2) + -3 4 + -23y = (-8 + -6y) + -3 Reorder the terms: 4 + -23y = -8 + -3 + -6y Combine like terms: -8 + -3 = -11 4 + -23y = -11 + -6y Solving 4 + -23y = -11 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 4 + -23y + 6y = -11 + -6y + 6y Combine like terms: -23y + 6y = -17y 4 + -17y = -11 + -6y + 6y Combine like terms: -6y + 6y = 0 4 + -17y = -11 + 0 4 + -17y = -11 Add '-4' to each side of the equation. 4 + -4 + -17y = -11 + -4 Combine like terms: 4 + -4 = 0 0 + -17y = -11 + -4 -17y = -11 + -4 Combine like terms: -11 + -4 = -15 -17y = -15 Divide each side by '-17'. y = 0.8823529412 Simplifying y = 0.8823529412
| 3-2(5x-1)=6+(8x+3) | | 4x^2+6x+54=0 | | 7n^2-60n-100=0 | | 2.8x-8x= | | -3x+4(2x+2)=3(5x-3)+7 | | X-10+2x+40=90 | | -x/2=5 | | 7r^2+16r-15=0 | | 5x+4=90 | | .5y+4=0.1428y | | 41-(3x+12)=3(x+5)+x | | 6x+12-4x=48 | | .5n=-8.3 | | x+163+38=2x+125 | | d/5=7 | | 2x^2+6x^2+6x=6x+40 | | 5n^2+34n-48=0 | | 5n^2+34-48=0 | | 9x^2+12+3=0 | | 3(4x^2-6x-7)=0 | | 10*54p= | | 4=0.4(3d-5-5) | | 43y=16 | | 2a^2-13a-7=0 | | 13(t+4)=2(t-10)-27 | | 2(4x+5)=-19+13 | | 4=0.4(3x-5-5) | | 11z/16+7z/8=5/15 | | 35=8x+138 | | .625j=-10 | | 6(y-8)-y=2(-9-y) | | x+x-40=90 |